The importance of early primary relationships in the development and psychoanalytic understanding of emptiness: connecting developmental theory with practice - Papadopoulos, Dimitrios (Frontiers in Psychiatry, 2025)
BackgroundEmptiness is an integral component of an individual’s psychic development, characterized by the subjective human existential experience of loss and disconnection from the self, other people, and the external world. More generally, emptiness reflects the quality of internalized object relationships and the intersubjective experience of early failures in affective attunement with a responsive and regulating other.AimThis article presents emptiness within the framework of object relations theory and incorporates Green’s concept of the “dead mother” experience. This paper aims to provide knowledge that can generate interest within the psychoanalysis community by illuminating the development and psychoanalytic understanding of emptiness, a complex condition that impacts individuals and societies.Case studyTo connect theory with practice, a case study of psychoanalytical psychotherapy with an adolescent girl is presented. This clinical paradigm focuses on the subject’s states of emptiness and nothingness, which are then projected onto the therapist who is attempting to contain and transform the girl’s painful emotions.ConclusionThe object relations theory and the dead mother concept both can offer a valuable psychoanalytic perspective for understanding the intersubjective experience of emptiness.